Recurrent Apthous Stomatitis (RAS) pada Mukosa Bibir Bawah yang Dipicu oleh Stress dan Kekurangan Zat Besi Tahap Awal - Safira Zahwa Anzali; Sartari Entin Yuletnawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Recurrent aphthous stomatitis (RAS) is one of the most common oral mucosal diseases, characterized by recurrent and painful ulcerations of the mobile or non-keratinized oral mucosa. These lesions are often found on the tongue, labial, and buccal mucosa. Clinically, RAS is divided into three types: minor, major, and herpetiform. The minor type is the most common and has smaller lesions, while the major type has larger lesions and often leaves scars. The herpetiform type is characterized by numerous small lesions appearing simultaneously. Factors influencing the immunological response in RAS include genetic predisposition, viral and bacterial infections, food allergies, vitamin and microelement deficiencies, systemic diseases, stress, and hormonal disorders. Several studies have shown that these factors can trigger or worsen the occurrence of RAS lesions. In addition, emotional and physical stress can contribute to increasing the frequency or duration of ulceration. A 36-year-old female patient presented with pain on the inside of the lower lip that had lasted for 10 days. An intraoral examination revealed a unilateral, yellowish-white ulcer on the inner lower lip surrounded by a distinct, reddish erythema. The lesion was approximately 2-3 mm in size, single in size, soft in consistency, and symptomatic. Based on these findings, the treatment plan includes a complete blood count (CBC), which measures various blood components, including red blood cells, white blood cells, and platelets. This examination is necessary to obtain further information regarding the cause of RAS in this patient. RAS is a multifactorial lesion that can occur in the oral mucosa. Supportive tests such as a complete blood count (CBC) are very useful in establishing the diagnosis and providing further guidance in planning appropriate therapy. Appropriate medication is expected to help the patient recover from complaints and prevent recurrence. Keywords : Recurrent Apthous Stomatitis, Laboratory, Stress